Diabetes care and outcomes of pediatric refugees and migrants from Ukraine and Syria/Afghanistan with type 1 diabetes in German-speaking countries - Auzanneau, Marie; Reinauer, Christina; Ziegler, Julian; Golembowski, Sven; de Beaufort, Carine; Schöttler, Hannah; Hahn, Eva; Mirza, Joaquina; Galler, Angela; Wurm, Michael; Holl, Reinhard W. (Frontiers in Endocrinology, 2024)
Introduction Currently, over two million war refugees live in Germany. Exposure to war and flight is associated with a high burden of diseases, not limited to mental disorders and infections. We aimed to analyze diabetes treatment and outcomes of pediatric refugees and migrants from Ukraine and Syria/Afghanistan with type 1 diabetes (T1D) in German-speaking countries. Materials and methods We included patients with T1D documented between January 2013 and June 2023 in the German/Austrian/Luxembourgian/Swiss DPV registry, aged < 20 years, born in Ukraine [U], in Syria or Afghanistan [S/A], or without migration background [C]. Using logistic, linear, and negative binomial regression models, we compared diabetes technology use, BMI-SDS, HbA1c values, as well as severe hypoglycemia and DKA rates between groups in the first year of treatment in the host country. Results were adjusted for sex, age, diabetes duration, and time spent in the host country. Results Among all patients with T1D aged < 20 years, 615 were born in Ukraine [U], 624 in Syria or Afghanistan [S/A], and 28,106 had no migration background [C]. Compared to the two other groups, patients from Syria or Afghanistan had a higher adjusted BMI-SDS (0.34 [95%-CI: 0.21–0.48] [S/A] vs. 0.13 [- 0.02–0.27] [U] and 0.20 [0.19–0.21] [C]; all p<0.001), a lower use of CGM or AID system (57.6% and 4.6%, respectively [S/A] vs. 83.7% and 7.8% [U], and 87.7% and 21.8% [C], all p<0.05) and a higher rate of severe hypoglycemia (15.3/100 PY [S/A] vs. 7.6/100 PY [C], and vs. 4.8/100 PY [U], all p<0.05). Compared to the two other groups, patients from Ukraine had a lower adjusted HbA1c (6.96% [95%-CI: 6.77–7.14] [U] vs. 7.49% [7.32–7.66] [S/A] and 7.37% [7.36–7.39] [C], all p<0.001). Discussion In their first treatment year in the host country, young Syrian or Afghan refugees had higher BMI-SDS, lower use of diabetes technology, higher HbA1c, and a higher rate of severe hypoglycemia compared to young Ukrainian refugees. Diabetologists should be aware of the different cultural and socioeconomic backgrounds of refugees to adapt diabetes treatment and education to specific needs.